Strategi Pengembangan Bisnis Rhythm of Empowerment Dengan Pendekatan Model Bisnis Kanvas - Budi Bagus Prasetyo; Lukman M. Baga; Lilik Noor Yuliati (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Rhythm of Empowerment (ROE) is a business division of PT. Cahaya Pagi, focusing on soft skills training. ROE is currently facing various challenges in competition, such as ways to achieve targeted working performance, acceleration in vision/mission accomplishment, and management of ROE human resources to face competition. The objective of this research was to design future ROE business model by using descriptive analysis method on a case study of ROE. The data were colected using Focus Group Discussions, interviews, observations, and literature study. Business model canvas (BMC) and SWOT analysis were used as analysis tools. The research results on customer segment showed an indication of segment expansion. Thus, the results also showed that the proportion value was added with product innovation, channels were strengthened in all lines, customer relationship was optimized by using IT, revenue stream was developed by creating other income, and organization was restructured to improve key human resources. Meanwhile, in the activities, some additional activities were added, key partnership was added with marketing partners and finance, tax, and production consultants. The cost structure was allocated to recruit new partners. In conclusion, ROE needs to improve 9 BMC elements of its current business model to the new BMC of ROE.Keywords: SWOT, BMC, soft skills training, value proposition, channelsAbstrak: Rhythm of Empowerment (ROE) adalah sebuah divisi bisnis dari PT. Cahaya Pagi yang bergerak di bidang pelatihan soft skills. Saat ini ROE memiliki berbagai kendala dan tantangan yang dihadapi antara lain bagaimana mencapai target kinerja dan melakukan akselerasi untuk mencapai visi dan misi perusahaan serta mengelola sumber daya ROE dalam menghadapi persaingan. Penelitian ini bertujuan merancang model bisnis di masa depan untuk ROE. Metode yang digunakan adalah analisis deskriptif studi kasus pada ROE, tehnik pengambilan data melalui Focus Group Discussion, wawancara, observasi dan studi literatur, sedangkan alat analisa menggunakan model bisnis kanvas (BMC) dan analisis SWOT. Hasil penelitian menunjukkan pada segmen pelanggan, terdapat perluasan segmen. Nilai proposisi ditambah dengan inovasi produk, saluran diperkuat disemua lini, hubungan pelanggan dioptimalkan melalui IT, arus pendapatan ditingkatkan dengan penciptaan pendapatan lain, restrukturisasi organisasi untuk perbaikan sumber daya kunci, sedangkan aktivitas kunci terdapat penambahan beberapa aktivitas, kemitraan kunci ditambah dengan mitra pemasaran dan konsultan keuangan, pajak serta produksi. Struktur biaya ditambahkan untuk perekrutan mitra-mitra baru. Maka dapat disimpulkan bahwa ROE perlu melakukan perbaikan terhadap 9 elemen BMC dari model bisnis saat ini yang dituangkan dalam BMC baru ROEKata kunci: SWOT, BMC, pelatihan soft skills, proporsi nilai, saluran